2015
DOI: 10.1186/s12978-015-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived behaviour control, attitude and empowerment on reported condom use and intention to use condoms among adolescents in rural Tanzania

Abstract: BackgroundDespite the declining trends of Human immunodeficiency virus (HIV) infection in Sub-Saharan Africa (SSA), unsafe sexual behaviours among adolescents still represent a public health challenge. It is important to understand factors acting at different levels to influence sexual behaviour among adolescents. This study examined the influence of perceived behaviour control, subjective norms, attitudes and empowerment on intention to use condoms and reported use of condoms among adolescents in rural Tanzan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
31
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 42 publications
8
31
3
5
Order By: Relevance
“…Future policy directions on family planning should focus on imparting knowledge on wider benefits of contraceptives and should target equally the urban and rural population. The role of positive attitudes in various health related behaviors is well documented [28][29][30]. We also found that there was a significant association between attitudes and contraceptive use.…”
Section: Discussionsupporting
confidence: 59%
“…Future policy directions on family planning should focus on imparting knowledge on wider benefits of contraceptives and should target equally the urban and rural population. The role of positive attitudes in various health related behaviors is well documented [28][29][30]. We also found that there was a significant association between attitudes and contraceptive use.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, our findings suggest that the young men have a strong belief in their own ability to use condoms consistently with every sexual encounter, this being supported by the significance of perceived behavioural control as a predictor of the intention to use condoms, which was similarly found in other studies (Kalolo & Kibusi, 2015;Lugoe & Rise, 1999). The reasons for this strong belief may be influenced by a number of factors.…”
Section: Discussionsupporting
confidence: 85%
“…In four studies in South Africa, Tanzania, Uganda and Swaziland, where norms were measured by different statements, social norms were shown to influence male and female adolescents’ use of condoms [10–13]. However, a study of adolescents in rural Tanzania that examined the role of social norms through statements including the following: “I agree with the opinion of my friends that I should use condoms when having sex” found that norms did not directly predict condom use [14]. These results are inconclusive and do not capture the full range of social norms that can influence behavior.…”
Section: Introductionmentioning
confidence: 99%